ANALISIS GENANGAN PADA PENGENDALIAN BANJIR SUNGAI SARIO KOTA MANADO - Utami, Panca Desy Puji (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Sangga Buana, 2024)
Sario River is located in Manado City and Minahasa Regency. The city of Manado is located on the northern tip of Sulawesi Island and is the largest city in the North Sulawesi as well known as the capital of North Sulawesi Province. The Geography coordinate is between 10o30'-10 o40' North latitude (N) and 1240 o 40'00